An overview of production, properties and prospects of tamarind seed oil biodiesel as an engine fuel. Issue 1 (31st December 2022) - Kumbhar, Vishal; Pandey, Anand; Varghese, Anil; Wanjari, Sourabh
ABSTRACT: Increasing energy consumption and minimisation of fossil fuels have motivated the researchers to probe biodiesel as a transportation fuel. However, large scale of biodiesel production has run into food versus fuel problem and hence efforts are being made to produce biofuel from non-edible sources. The present article focuses on the potential and prospects of biodiesel made from tamarind seeds, which are known as waste product and can be thought to be an alternative energy source. Tamarind seed oil biodiesel possesses excellent combustion properties and can be sanctioned for its adoption in engine. Moreover, the tamarind seed oil biodiesel is environment-friendly and can contribute in the reduction of carbon emission when used as an engine fuel. A summary of tamarind seed oil biodiesel has shown that the total greenhouse gas emission can be reduced greatly. Overall future of tamarind seed oil biodiesel largely depends on plantation, pricing and establishing of low-cost biodiesel production technologies.